SOCIAL FUNCTIONING OF COMMUNITY SUNDA WIWITAN TRADITION OF PASIR VILLAGE, GARUT DISTRICT, WEST JAVA - Nike Vonika (Politeknik Kesejahteraan Sosial Bandung, 2024)
This study describes the social functioning of the Sunda Wiwitan indigenous community of Pasir Garut Village, which is a community that adheres to local beliefs. This study was conducted using a descriptive qualitative methodology. The results of the study illustrate that the adherents of the Sunda Wiwitan local belief in Garut do not experience significant obstacles in being able to function socially in society even though they have different identities. They understand that the results of the judicial review convince them that the government has recognized their existence, although they realize that there are still differences in treatment in the administration of civil registration, but there are other alternatives that can be done so that there is a cessation of their lives and they can function socially